Piping System Stress Analysis on Gas Compressor Station (Case Study: Gas Compressor Station at Pondok Tengah) - BANI PERWIRA (NIM 13104160), YOSEPHUS
Today, natural gas is one of the alternative energy which can substitute the uses of fuel oil for main energy. For this reason, it is necessary to build a processing station which can improve the production capacity of natural gas. Mechanical design on piping system at natural gas processing station is needed to avoid failures. These failures can be avoid by conducting a good analysis and calculation to the all aspects based on Code and Standard for piping system. In this final project, piping system stress analysis on gas compressor station at Pondok Tengah has been done. In this analysis, piping system modelling has been developed using AutoPIPE software and based on ASME B31.3 Process Piping. The stress analysis result shows that support modification for piping system is needed because of the unability of piping system to hold the sustained loads. The chart of stress analysis result caused by occasional loads shows that failures initially occur when wind load over 210 km/h, earthquake load over 3 Richter scale, and anchor movement at MP Suction Scrubber over 0,6 m. The stress analysis result caused by expansion loads shows that stresses on all segment of piping system are appropriate with the allowable stress. The effect of pressure and temperature rise on one of the discharge compressor piping shows that failures initially occur when pressure rise over 782 psi and temperature rise over 400 oF.